2021
DOI: 10.3390/polym13152559
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Capture Utilization for Biopolymer Foam Manufacture: Thermal, Mechanical and Acoustic Performance of PCL/PHBV CO2 Foams

Abstract: Biopolymer foams manufactured using CO2 brings a novel intersection for economic, environmental, and ecological impact. PHBV has a low solubility in CO2 while PCL has a high CO2 solubility. In this paper, PCL is used to blend into PBHV and unfoamed and foamed systems are examined. Foaming the binary blends at two depressurization stages with subcritical CO2 as the blowing agent, produced open-cell and closed-cell foams with varying cellular architecture at different PHBV concentrations. Differential Scanning C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 85 publications
(115 reference statements)
0
7
0
Order By: Relevance
“…PHBV is biologically compatible and presents higher flexibility, ductility, and toughness than P3HB [351]. Moreover, PHBV shows barrier properties to water and air, making it a potential candidate for disposable packages and other uses [352].…”
Section: Poly-hydroxyalkanoates (Phas)mentioning
confidence: 99%
See 1 more Smart Citation
“…PHBV is biologically compatible and presents higher flexibility, ductility, and toughness than P3HB [351]. Moreover, PHBV shows barrier properties to water and air, making it a potential candidate for disposable packages and other uses [352].…”
Section: Poly-hydroxyalkanoates (Phas)mentioning
confidence: 99%
“…Polymer blending was also used as a technique to improve some of the properties of PHVB that are important in foaming, such as low melt viscosity and high crystallinity. Examples include blending PHBV with PCL [352,453], which is a semi-crystalline polymer with high miscibility in CO 2 , with PBAT [376], and with PLA [128,251]. Jenkins et al [453] showed that PHBV and PCL are immiscible when blended using mechanical means, but the same blends were miscible when produced using supercritical methods.…”
Section: Biodegradable Polymer Blendsmentioning
confidence: 99%
“…In the last few years, different blowing procedures have been used to reduce PHBV's brittleness and production costs [7,25,27,28]. Particulate leaching is a popular technique often used to obtain high-porosity biopolymer foams for biomedical purposes, but it is rarely employed to obtain PHBV foams due to the chlorinated derivatives used as solvents and the extensive washing required by this technique [7,25].…”
Section: Introductionmentioning
confidence: 99%
“…Particulate leaching is a popular technique often used to obtain high-porosity biopolymer foams for biomedical purposes, but it is rarely employed to obtain PHBV foams due to the chlorinated derivatives used as solvents and the extensive washing required by this technique [7,25]. The use of supercritical (sCO 2 ) or subcritical carbon dioxide as a physical blowing agent has become a preferred option in recent years due to its nontoxicity and nonflammability [28]. PHBV/polycaprolactone blend foams with open and closed cells were obtained using subcritical CO 2 as a blowing agent [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation